2010 East-West Design &Amp; Test Symposium (EWDTS) 2010
DOI: 10.1109/ewdts.2010.5742135
|View full text |Cite
|
Sign up to set email alerts
|

Advanced modeling of faults in Reversible circuits

Abstract: This survey provides an overview of some recent developments in the testing and design validation of reversible logic circuits Reversible circuits are of interest in ultra-lowpower design and in quantum information processing. We describe the fault and error models that have been proposed for these circuits and summarize their properties. We also discuss algorithms for automatic test pattern generation, design-fortestability techniques, and design debugging. We conclude by briefly examining the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In other words, we can consider the missing as buffering the inputs on the outputs. On the other hand, a repeated gate fault leads to replacing a gate with two consecutive gates of the same type, but the order of connection is same for both gates [19]. …”
Section: A Missing/repeated Gate Faultmentioning
confidence: 98%
See 3 more Smart Citations
“…In other words, we can consider the missing as buffering the inputs on the outputs. On the other hand, a repeated gate fault leads to replacing a gate with two consecutive gates of the same type, but the order of connection is same for both gates [19]. …”
Section: A Missing/repeated Gate Faultmentioning
confidence: 98%
“…However, it is shown that this model is not well suited for reversible circuits. Fault models for reversible circuits have been reviewed in [19]. New logical fault models based on the concepts of missing and repeated logic gate at logical level have been introduced in [11], [12].…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers [9][10][11][12] have studied the problem of fault modelling and testing of reversible logic circuits. While the stuck-at fault model is widely used for conventional logic circuits, newer models such as single missing-gate fault (SMGF), repeated-gate fault (RGF), partial missing-gate fault (PMGF), or multiple missing-gate fault (MMGF), have been found to be more suitable for representing physical failures or defects in reversible circuits implemented with quantum technologies [9,11,12]. We follow the fault models as described in the literature as fruitful to capture physical defects in quantum reversible circuits [4,9,11,13].…”
Section: Introductionmentioning
confidence: 99%